Politics lost in translation: The African concept of time as a method to understand African conflicts - Ramy Magdy (Review of Economics and Political Science (REPS), 2020)
Purpose - This paper aims to explore John Mbiti's concept of African time in line with the studies on the crisis of the post-independence African state. Then, how this concept offers new analytical spaces for understanding the modern nation-states inconveniences in African contexts. Design/methodology/approach - The paper analyses the Mbitian African concept of time in light of the works on post-independence African state and communalism. Findings - By using the Mbitian concept of time politically after explaining African communalism and African concepts of personhood and destiny, the paper reached a conclusion. This conclusion claims that due to the highly existential nature of the African concept of destiny and the past-oriented feature of the African concept of time, Africans cannot be restrained by any supernatural claim or any futuristic promises that are irrelevant to their context and cut from the communal values of ancestral past. Africans do not think supernaturally or bet for the future. However, those futuristic and supernatural claims that cannot restrain the African subjectivity - ironically - characterize the modern nation state with its "progress orientation" and "social-contract" metaphysics. Unfortunately, this radical difference in perceptions between the past-oriented African temporality and the future-oriented modern state temporality rendered the post-independence. African state dysfunctional and unable to operate as a medium for authority. This, consequently, opened the door for informal conflict and strife. Originality/value - The paper is novel with regard to offering a new theory on the conceptual problems of the nation state in African contexts.
Keywords: 330; Africa; Politics; Time; Metaphysics; Conflicts; Temporality; Sasa; Zamani; Personhood; Communalism; Destiny; Ori